Management Of Ulcerative Colitis Vis-À-Vis Atisara And Its Manifestations : An Ayurvedic Review - Suden, Akshay (International Research Journal of Ayurveda & Yoga, 2020)
In Modren system of medicine no specific cause for the occurrence of ulcerative colitis is known. No permanent cure of this disease is, presently available, only management measures geared towards securing a remission and prolonging its period, are, generally aimed at. Such a situation is often achieved by resorting to steroids, strong antibiotics, etc. The harmful effects of this therapy are well documented. While in the Ayurvedic system of medicine: the symptoms of the prominent manifestations of Atisara viz. Pittaja-Atisara, Raktaja-Atisara, Pravahika (Pittaja, Raktaja), Grahani (Pittaja, Raktaja) resemble greatly with those of ulcerative colitis. Ayurveda has a repository of medications, of proven worth suitable for each of these manifestations of Atisara. Besides their curative power, they are systemic, most beneficial, and the least harmful, and are capable of rooting out the disease. Two practically useful suggestions have been recommended for managing the ulcerative colitis